INNV-25. ASSESSING SLEEP AND CIRCADIAN RHYTHMS IN PRIMARY BRAIN TUMORS PATIENTS: AN OBSERVATIONAL STUDY. (14th November 2022) - Wollet, Alex; Leeper, Heather; Vera, Elizabeth; Mentges, Kelly; King, Amanda; Rogers, James; Sass, Dilorom (Delia); Acquaye, Alvina; Adegbesan, Kendra; Boris, Lisa; Burton, Eric; Celiku, Orieta; et al.
Abstract: Sleep-wake disturbances are among the most common and severe symptoms in primary brain tumor (PBT) patients. Currently, no studies have quantified their physiological sleep measurements or compared these assessments to established patient reported outcome measures (PROs). Smart wearable devices, such as Fitbits, continuously monitor patient behaviors at home and provide detailed physiological measurements of sleep, activity, and heart rate. We hypothesized that smart wearable devices can accurately determine physiological sleep disturbances and circadian disruptions and will complement established PROs in a PBT patient population. This observational, cross-sectional trial monitors sleep and circadian rhythm variables using Fitbit smart wearable devices worn for 1 month. Additionally, participants will answer PROs questionnaires (PROMIS Sleep Disturbance and Sleep Related Impairment-Short Forms, Sleep Hygiene Index, Morningness-Eveningness questionnaire, and Consensus Sleep Diary) at study entry and during the last week on-study. The present study is a planned interim analysis of 54 patients to assess feasibility, including evaluation of enrollment, attrition, study parameter completion and data missingness. 73 PBT patients were screened and approached. Of these patients, 54 (74%) were enrolled on study and 19 (26%) declined participation (8 lacked interest, 3 discomfort wearing watches, 3 lacked smart phone, 2 unable to wear device at work, 2 unable to attend consent calls, 1 pregnancy and 1 cognitive complication). The accrued patients were 56% male, 56% ³ 50 years of age, and 81% had a KPS ³ 90. Patients represented different stages of treatment: 6% of patients were newly diagnosed, 24% on active treatment (11% 1 st recurrence, 13% 2 nd recurrence), and 70% were on imaging surveillance. Feasibility was confirmed as there were no deviations reported and 100% of PROs and study timepoints completed. Quantified Fitbit data including percent time worn and physiologic sleep parameters will be reported. Study enrollment for efficacy measures continues.